2011
DOI: 10.1136/jramc-157-02-05
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated Febrile Illnesses Amongst British Troops in Helmand, Afghanistan

Abstract: These cases probably represent the "tip of an iceberg" for British and Allied forces. More resources for diagnostic facilities and follow-up of patients are required to improve the management and surveillance of "Helmand Fever" cases; until then doxycycline 100 mg twice daily for 2 weeks should be given to all troops who present with an undifferentiated febrile illness in Helmand, Afghanistan. Patients with acute Q fever should be followed-up for at least 2 years to exclude chronic Q fever. Prevention of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 37 publications
1
42
0
2
Order By: Relevance
“…A study performed on British soldiers with fever of unknown origin in Afghanistan showed that 26% of the 26 soldiers had acute Q fever (9). This issue should be taken into account due to several factors such as the proximity of Iran (Sistan and Baluchestan Province) to Afghanistan, the entry of immigrants (legal and illegal) and livestock to Sistan and Baluchestan Province, lack of adequate control of the production and distribution chain of dairy products, and, finally, traditional ranching methods and proximity of livestock and ranchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study performed on British soldiers with fever of unknown origin in Afghanistan showed that 26% of the 26 soldiers had acute Q fever (9). This issue should be taken into account due to several factors such as the proximity of Iran (Sistan and Baluchestan Province) to Afghanistan, the entry of immigrants (legal and illegal) and livestock to Sistan and Baluchestan Province, lack of adequate control of the production and distribution chain of dairy products, and, finally, traditional ranching methods and proximity of livestock and ranchers.…”
Section: Discussionmentioning
confidence: 99%
“…There are some published studies of countries neighboring Iran in relation to prevalence of Q fever (4,(9)(10)(11). Therefore, the aim of this study was to investigate the presence of anti-C. burnetii antibodies among febrile patients in southeast Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2007 and 2010, the largest described outbreak of Q fever occurred in the Netherlands, resulting in .4000 human cases, and .50 000 goats were culled in order to control the spread of the disease (Whelan et al, 2011;Dijkstra et al, 2012). In addition, there are several recent reports of outbreaks amongst military personnel serving in Iraq and Afghanistan, and C. burnetii is listed as a category B agent by the US Centers for Disease Control and Prevention (Moodie et al, 2008;Faix et al, 2008;Bailey et al, 2011). Infection of humans usually occurs by inhalation of bacterial aerosols, but transmission by ingestion of contaminated dairy products has been reported (Madariaga et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…AvBat from Argas vespertilionis, bat ticks in Southern France (Socolovschi et al, 2012a). In addition, new discoveries such as the detection of rickettsial agents in mosquito vectors (Socolovschi et al, 2012b,c); the high level of rickettsial etiology in febrile patients in rural sub-Saharan Africa, Afganistan, or Nepal (Maina et al, 2012;Pradhan et al, 2012;Bailey et al, 2011); the possibility of the plant-mediated transmission route of endosymbiotic Rickettsia (Caspi-Fluger et al, 2012) open new issues in the rickettsial field. In the case of rickettsial projects in Slovakia, preparation and prevention are the main tasks for future.…”
Section: Resultsmentioning
confidence: 99%